A Single-Crystal Neutron Diffraction Study on Magnetic Structure of the Quasi-One-Dimensional Antiferromagnet SrCo2V2O8 - 刘娟娟 汪晋辰 罗伟 盛洁明 何长振 S. A. Danilkin 鲍威 (中国物理快报：英文版, 2016)
The magnetic structure of the spin-chain antiferromagnet SrCo2 V208 is determined by single-crystal neutron diffraction experiment. The system undergoes a long-range magnetic order below the critical temperature TN=4.96 K. The moment of 2.16#B per Co at 1.6K in the screw chain running along the c axis Mternates in the c axis. The moments of neighboring screw chains are arranged antiferromagnetically along one in-plane axis and ferromagnetieally Monk the other in-plane axis. This magnetic configuration breaks the four-fold symmetry of the tetragonM crystal structure and leads to two equally populated magnetic twins with the antiferromagnetic vector in the a or b axis. The very similar magnetic state to the isostructural BaCo2 V~ 08 warrants SrCo2 V2 08 as another interesting half-integer spin-chain antiferromagnet for investigation on quantum antiferromagnetism.